Basic petrophysics of the Precuyano Cycle, Cara Cura hills, Mendoza (Latin American Journal of Sedimentology and Basin Analysis, 2021)
In the ninetieth, the discovery of hydrocarbons in volcanic or volcaniclastic rocks was not consid- ered economically viable in the petroleum explora- tion because of the lack of reservoir quality. However, during last decades many examples from our country proved to be real targets like, Campo Océano, Octógono, Cupén Mahuida (Sruoga et al., 2004; Sruoga and Rubinstein, 2007; Schiuma et al., 2011; Velo et al., 2014). These latter and the need to increase gas/oil production challenged industry to deepen into the knowledge of the pore structure of their deposits.Volcanic and volcaniclastics deposits can develop porosity in different ways. The more elemental process that lead to the possible formation of porosity takes place once fragments have been ejected from the volcano edifice. As they are deposited mechanically by gravity or fluid transport, porosity results from the degree of sorting of fragments and their type of packaging. After deposition pore space will be modified by diagenetic processes being the more important burial and compactation and cement/clay formation similar to clastics deposits. But unlike typical sedimentary rocks, the nature and style of the eruption and subsequent cooling of these rocks add significant controlling factors over the evolution of the porosity. Some of the most relevant are the alteration of chemically unstable minerals during volcanic processes, the welding of hot material after deposition and fracturing due to cooling. Primary porosity comprises gas voids, vesicles, intergranular pores and some cooling joints; secondary porosity includes intracrystalline dissolution, matrix dissolu- tion pores, fractures, fissures, weathering cracks and interstices. The secondary porosity is frequently the only kind present and may be the result of hydrothermal alteration, fracturing and late-stage diagenetic mineral alteration.The main purpose of this contribution is to characterize a volcaniclastic and volcanic sequence of the Precuyano Cycle in the north flank of Sierra de la Cara Cura, Neuquén Basin (Fig. 1). The region holds block and ash flows and lava facies detailed previously by Drosina et al. (2017) (Fig. 2, 3). Re- sults of core observation, thin section analysis and scanning electronic microscope (SEM) indicate that the quality of volcanic rock reservoirs is controlled not only by their lithofacies but also by the diagenetic and tectonic processes affecting them. Detailed petrophysical laboratory studies permitted us to additionally arrive to numerical values of the porosity and permeability of the most representative levels of volcaniclastics and volcanic deposits of the Precuyano Cycle.The volcaniclastics levels are composed of block and ash deposits (Figs 2 and 3). There are poorly sorted, massive mixtures of decimeter- to meter-sized blocks set within a fine lapilli to medium ash-grade matrix; thickness range from 12.50 to 0.95 meters in the SE-NW direction. Primary porosity is controlled by vesiculation in the andesitic pyroclasts and some and scarce columnar jointing. Secondary porosity is represented by micro structures in the andesitic blocks frequently filled-in with iron oxides. Meso- fractures are prevalent and cut through multiple lava flows and block and ash deposits. Another secondary porosity corresponds to crystalloclast dissolution with the consequent intracrystalline and vuggy types porosities (0.004 – 0.62 mm, micropores) (Fig. 4). The effective porosity and permeability to gas, for the sequence varies between 9.7 to 21.46% and 0.288 to 1.339 mD respectively (Table 1 and Fig. 8).The volcanic levels are composed of abundant tabular andesitic flows facies that are laterally continuous along several kilometers (Figs. 2 and 3). Their thicknesses range from 5.2 to 8.4 meters. Individual lava flows can be divided into base, core and top facies, with lava piles comprising repeated cycles of these distinct facies. The best reservoir quality concerning primary porosity occurs in andesitic flow tops where vesicular interconnected porosity dominates but significantly decreases to the core of due to compactation and mineral alteration. Secondary porosity results mainly from jointing and fracturing from both tectonic and long-lasting coo- ling. They cut throughout multiple flows to connect the flow tops (the favorable reservoir) horizons and even with the flow core. Syn- and post-depositional hydrothermal alteration induces a hydraulic local fracture network. Weathering alteration products also fill-in open spaces like dissolution cavities, vesicles, fractures and form mineral aggregates as part of phenocrystal replacement (Figs. 4 and 5). The effective porosity and permeability to gas, for the sequence varies between 8.6 and 19.5%, 0.014 and0.009 mD with anomalous values of up to 32.182 mD (Table 1 and Fig. 6).The results obtained herein permit to propose the existence two types of reservoirs in the Precuyano Cycle of the Cara Cura depocenter. One observed in the volcaniclastics deposits that proved to be complex enough to be compare with that observed in fractured carbonate reservoirs and the other is associated with the volcanic deposits. Significant pore reduction was observed in numerous levels results from compactation, tuff welding and mineral alteration, commonly of sericite type, induced by the volcanic process itself and by diagenesis. These latter point to a grade of “uncertainty” when exploring and producing these oil fields due to the resulting lateral and vertical heterogeneities in the texture and structure of the rock bodies that greatly condition the drilling and seismic operations and lately, the production programs.
Keywords: Volcaniclastics rocks, Porosity, Permeability, Precuyano Cycle.